Multimodal mechanism of action of allosteric HIV-1 integrase inhibitors - Jurado, Kellie Ann (2013)
Integrase (IN) is required for lentivirus replication and is a proven drug target for the prevention of AIDS in HIV-1 infected patients. While clinical strand transfer inhibitors disarm the IN active site, allosteric inhibition of enzyme activity through the disruption of IN-IN protein interfaces holds great therapeutic potential. A promising class of allosteric IN inhibitors (ALLINIs), 2-(quinolin-3-yl) acetic acid derivatives, engage the IN catalytic core domain dimerization interface at the binding site for the host integration co-factor LEDGF/p75. ALLINIs promote IN multimerization and, independent of LEDGF/p75 protein, block the formation of the active IN-DNA complex, as well as inhibit the IN-LEDGF/p75 interaction in vitro. Yet, rather unexpectedly, the full inhibitory effect of these compounds is exerted during the late phase of HIV-1 replication. ALLINIs impair particle core maturation as well as reverse transcription and integration during the subsequent round of virus infection. Recapitulating the pleiotropic phenotypes observed with numerous IN mutant viruses, ALLINIs provide insight into underlying aspects of IN biology that extend beyond its catalytic activity. Therefore, in addition to the potential to expand our repertoire of HIV-1 antiretrovirals, ALLINIs afford important structural probes to dissect the multifaceted nature of the IN protein throughout the course of HIV-1 replication.